HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KECEPATAN TERHADAP KEMAMPUAN SHOOTING DALAM PERMAINAN SEPAKBOLA PADA SSB UNIVERSITAS RIAU U-15 - Wandi Dedi Saputra; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was conducted to know and determine there is any correlation between leg muscle stenght and speed to the shooting capability in football players SSB U15 university of riau. Kinds of this research is a correlation with a member ia 20 people’s. the technique of taking that using total sampling . so that the member os samples in this study normal. From the calculation that is know that there is a significant relationship between the variables X1, X2 and Y correlation leg muscle strength trought the shooting abililty of football players SSB U15 university of riau. The result froomthe correlation calculation in fount that y value of 0,631 from table r is fount table r is found table r value (0.456) its means that the value of rarimatict 0,630>rtable (0,456) there is any correlation between leg muscle strength and speed to the shooting capability in football player SSB U15 at the university of riau the result from the results from the correlation is found that raritmatic as 0,891. From the tablethe value of the value of R in R table with significance level. (A) 0.05 = 0,456. Is mean that the value rarimatic 0.891>(0,456)Keywords: Leg muscle strength, Speed, Shooting ability, soccer